Valorization of a spent lithium-ion battery electrolyte through syngas formation using CO2-assisted catalytic thermolysis over a battery cathode material. Issue 50 (August 2021) - Jung, Sungyup; Kwon, Dohee; Park, Sanghyuk; Kwon, Kyungjung; Tsang, Yiu Fai; Kwon, Eilhann E.
Graphical abstract: Highlights: A new valorization platform for lithium-ion battery electrolyte was suggested. Thermolysis of battery electrolyte produced complicated liquid/gas mixtures. CO2 promoted gas phase reactions for additional CO formation. Catalytic thermolysis converted entire battery electrolyte into H2 and CO. LiNi0.8 Co0.1 Mn0.1 O2 (cathode) was active for chemical bond scission, forming syngas. Abstract: Development of rechargeable batteries in energy storage systems and electric/electronic devices has been rapidly progressed as an effort to amplify the utilization renewable and sustainable energies since the past few decades. However, increasing demand of the rechargeable batteries results in significant accumulation of battery waste materials. In the current battery recycling process, the recovery of cathode metal(oxide)s has been mainly focused, but other organic compartments were not properly recycled. In this study, the valorization of battery electrolyte was investigated. To this end, CO2 -assisted thermolysis of a broadly used battery electrolyte, LiPF6 in carbonate solvents, was performed. First part examined liquid (carbonates, cyclic and aliphatic hydrocarbons) and gaseous products (H2, CO, CH4, C2 H4, and CO2 ) from thermolysis of battery electrolyte at different conditions. The complicated mixture of pyrogenic products needs additional separation processes to recover each compound. To convert the complicated mixture samples into value-added chemicals ( i.e., syngas), catalytic thermolysis was done in the second part. Considering that the practical pyrolysis condition of battery electrolyte includes a cathode material during the thermolysis, a conventional cathode material (NCM 811: LiNi0.8 Co0.1 Mn0.1 O2 ) was used as a catalyst. It was highly active to convert entire liquid compounds into syngas at ≤ 500 °C, and synergistic effects of catalyst and CO2 resulted in enhanced CO formation. Given that the metallurgy process for battery operates at near 1300 °C, thermolysis of battery electrolyte could be incorporated into the metallurgy process to maximize recovery of organic and metallic compounds in spent batteries.